Ph-cycling models for in vitro evaluation of the efficacy of fluoridated dentifrices for caries control: Strengths and limitations - Buzalaf, Marília Afonso Rabelo; Hannas, Angélica Reis; Magalhães, Ana Carolina; Rios, Daniela; Honório, Heitor Marques; Delbem, Alberto Carlos Botazzo [UNESP] (FapUNIFESP (SciELO), 2010)
Despite a plethora of in situ studies and clinical trials evaluating the efficacy of fluoridated dentifrices on caries control, in vitro pH cycling models are still broadly used because they mimic the dynamics of mineral loss and gain involved in caries formation. This paper critically reviews the current literature on existing pH-cycling models for the in vitro evaluation of the efficacy of fluoridated dentifrices for caries control, focusing on their strengths and limitations. A search was undertaken in the MEDLINE electronic journal database using the keywords pH-cycling, demineralization, remineralization, in vitro, fluoride, dentifrice. The primary outcome was the decrease of demineralization or the increase of remineralization as measured by different methods (e.g.: transverse microradiography) or tooth fluoride uptake. Inclusion of studies, data extraction and quality assessment were undertaken independently and in duplicate by two members of the review team. Disagreements were solved by discussion and consensus or by a third party. One hundred and sixteen studies were included, of which 42 addressed specifically the comparison of dentifrices using different pH-cycling models. The other studies included meta-analysis or reviews, data about the effect of different fluoride sources on de-remineralization, different methods for analysis de-remineralization and chemical variables and characteristics of dental hard tissues that might have influence on de-remineralization processes. Generally, the studies presented ability to detect known results established by clinical trials, to demonstrate dose-related responses in the fluoride content of the dentifrices, and to provide repeatability and reproducibility between tests. In order to accomplish these features satisfactorily, it is mandatory to take into account the type of substrate and baseline artificial lesion, as well as the adequate response variables and statistical approaches to be used. This critical review of literature showed that the currently available pH-cycling models are appropriate to detect dose-response and pH-response of fluoride dentifrices, and to evaluate the impact of new active principles on the effect of fluoridated dentifrices, as well as their association with other anti-caries treatments.
Keywords: Dental caries; Dentifrices; Efficacy; Fluorides; In vitro